Economic and Policy Foundations for Growth in South East Europe: Remaking the Balkan Economy - Bennett, Adam.; Kincaid, G. Russell; Sanfey, Peter; Watson, Max.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
This volume argues that a renewed commitment to sound macroeconomic policies and structural reforms is needed for countries in South East Europe, or 'the Balkans' achieve to sustainable prosperity, along with enhanced support from the international community. New fiscal and financial architecture has valuable lessons for policymakers in SEE.
Keywords: Political science; Political economy; Comparative politics; Public policy; Peace; Macroeconomics; Political Science and International Relations; Conflict Studies; Macroeconomics/Monetary Economics//Financial Economics; Comparative Politics; Public Policy; Political Economy; Political Science; Electronic books